2011
DOI: 10.1136/aim.2010.002915
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Acupuncture and Postoperative Acupressure Can Prevent Postoperative Vomiting following Paediatric Tonsillectomy Or Adenoidectomy: A Pragmatic Randomised Controlled Trial

Abstract: Objective To investigate the effectiveness of acupuncture and acupressure as supplements to standard treatment for postoperative vomiting in children undergoing tonsillectomy and/or adenoidectomy. Methods A pragmatic, open, block-randomised controlled trial. The results were analysed according to the intention-to-treat principle. The study was conducted without extra resources in a normal setting at the day-surgery department of Lovisenberg Diakonale Hospital in Oslo. 154 children with an American Society of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…[52][53][54][55][56][57][58][59][60] One study found acupuncture partly effective for pain, 61 and one study found acupressure effective for vomiting, but not nausea.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[52][53][54][55][56][57][58][59][60] One study found acupuncture partly effective for pain, 61 and one study found acupressure effective for vomiting, but not nausea.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported the need for rescue medication 52,61,62 64,66 and five reported adverse events. 37,53,57,59,63 Discomfort and treatment satisfaction were reported twice. 37,59,60,62 Resumption to normal activity, complete response, emergence agitation, parent satisfaction, and recovery time were reported once each.…”
Section: Norheim Et Almentioning
confidence: 99%
See 3 more Smart Citations